2018
DOI: 10.1016/j.ijpddr.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

UDP-glycosyltransferase family in Haemonchus contortus: Phylogenetic analysis, constitutive expression, sex-differences and resistance-related differences

Abstract: UDP-glycosyltransferases (UGT), catalysing conjugation of UDP-activated sugar donors to small lipophilic chemicals, are widespread in living organisms from bacteria to fungi, plant, or animals. The progress of genome sequencing has enabled an assessment of the UGT multigene family in Haemonchus contortus (family Trichostrongylidae, Nematoda), a hematophagous gastrointestinal parasite of small ruminants. Here we report 32 putative UGT genes divided into 15 UGT families. Phylogenetic analysis in comparison with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 48 publications
2
37
0
Order By: Relevance
“…Although induced expression of certain DMEs in resistant isolates in comparison to sensitive ones has been reported repeatedly [5,6,12,14], the mechanisms and circumstances of this induction have not been elucidated. As the contact of nematodes with sub-lethal doses of anthelmintics may play an important role, we incubated ex vivo H. contortus adults from ISE strain (sensitive to all anthelmintics) with the anthelmintic drug albendazole (ABZ) and its active metabolite ABZ-sulfoxide (ABZSO) at three sub-lethal doses for 4 and 12 h. Two different incubation duration were used because it is known that the time required to induce different DMEs differs significantly [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although induced expression of certain DMEs in resistant isolates in comparison to sensitive ones has been reported repeatedly [5,6,12,14], the mechanisms and circumstances of this induction have not been elucidated. As the contact of nematodes with sub-lethal doses of anthelmintics may play an important role, we incubated ex vivo H. contortus adults from ISE strain (sensitive to all anthelmintics) with the anthelmintic drug albendazole (ABZ) and its active metabolite ABZ-sulfoxide (ABZSO) at three sub-lethal doses for 4 and 12 h. Two different incubation duration were used because it is known that the time required to induce different DMEs differs significantly [29].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-two isoforms of UGTs, the most important Phase II enzymes catalyzing conjugation of UDP-activated sugar donors to small lipophilic chemicals, were identified in H. contortus genome. Constitutive expression of isoform UGT368B2 was significantly higher in H. contortus resistant strains than in the sensitive strains [12].…”
Section: Introductionmentioning
confidence: 85%
“…Although no consistent pattern was observed regardless of drug and concentration used, we found downregulation of several members of the phase II enzymes of the UGT family. In contrast, several studies have shown an increased expression and activity of UGTs in benzimidazole-resistant strains of H. contortus [29,63]. Although the expression and function of phase I and phase II enzymes have been investigated in parasitic helminths, few studies have focused on ascarid worms and thus further investigation is required.…”
Section: Gene Id Superfamily Log2fcmentioning
confidence: 99%
“…While this protein is larger than the predicted size, it is within Hb-ugt-1 a range that could be attributed to post-translational modification. Other helminths also produce multiple isoforms of UDP-glycosyltransferases 27 , which may be the case with H. bacteriophora and could alternatively explain the size discrepancy.…”
Section: Discussionmentioning
confidence: 99%